Faktor Yang Berhubungan Dengan Kejadian Penyakit Hiperbarik Pada Nelayan Penyelam Tradisional Di Kelurahan Bajoe Kabupaten Bone - Ruhban, Andi; Arif, Muh. Ikbal; Oktavia, Oktavia; Iskandar, A. AR. Rakhmansya (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Hyperbaric disease is one of the health problems experienced by traditional diving fishermen in their work environment caused by a high-pressure environment that is more than one atmosphere.This study aims to determine the factors associated with the incidence of hyperbaric disease in traditional diving fishermen in Bajoe Village. This type of research is an analytical survey with a cross sectional approach. The sampling technique uses simple random sampling of 66 people. Data analysis using chi square test and odds ratio.The results showed that of the 4 independent variables studied, there were 3 associated with the incidence of hyperbaric disease, namely depth (p = 0.001) (OR = 5.417; CI 95%= 1.862 – 15.7), tenure (p=0.001) (OR= 8.750; CI 95%= 2.265 – 35.362) and PPE usage (0.005) (OR= 0.233; CI 95%= 0.081 – 0.668), 1 unrelated variable i.e. dive duration (p= 0.605) (OR= 1.326; CI 95%= 0.454 – 3.877).The conclusion of this study is that there is a relationship between depth, length of work, use of PPE and there is no relationship between diving duration and the incidence of hyperbaric disease. So, it is hoped that the Puskesmas and local fishermen divers can work together to hold socialization related to hyperbaric disease factors. Keywords : Hyperbaric Disease, Fisherman diver, Depth, Tenure, Diving Time, PPE